Peran Keteladanan Guru PAI dalam Menginternalisasi Nilai-Nilai Akhlakul Karimah Peserta Didik Perspektif Abdullah Nashih Ulwan - Elis Ayu Islamia; Muhammad Fahmi; Fathur Rohman (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to analyze the role of Islamic Education (PAI) teachers' exemplary behavior in internalizing noble moral values (akhlakul karimah) in students from the perspective of Abdullah Nashih Ulwan. Exemplary conduct is an effective educational method in shaping students' character, particularly regarding moral and spiritual values. Abdullah Nashih Ulwan emphasizes the importance of morality and exemplary behavior as the core of Islamic education. This research employs a qualitative approach with a descriptive-analytic method, using Ulwan's works as primary sources and observations of teachers' practices in schools. The findings indicate that teachers' exemplary behavior significantly influences students' attitudes, behavior, and morality. Teachers who exemplify good conduct through their words, actions, and daily attitudes create a conducive learning environment for the internalization of noble moral values. This study recommends strengthening teachers' competencies in exemplary behavior and enhancing students' understanding of the importance of noble morals in daily life.